Factors related to HbA1c in the first trimester of pregnancy - Sumarah, Sumarah; Anies, Anies; Rahfiludin, Mohammad Zen; Sulistiyani, Sulistiyani (International Journal of Public Health Science (IJPHS), 2023)
The prevalence of gestational diabetes mellitus (GDM) in the world is 16.2% of live births associated with hyperglycemia in pregnancy, and 7.4% are caused by type 1 or 2 diabetes which is detected for the first-time during pregnancy. The prevalence of GDM in Indonesia reaches 3.6% and the highest rate is found in the Special Province of Yogyakarta (2.6%). One of the risk factors for GDM is excess nutrition which is influenced by daily intake. This study aims to determine the relationship between nutritional intake and body mass index (BMI) with HbA1c levels in first-trimester pregnant women. This study used a cross-sectional design. A simple random sampling with inclusion and exclusion criteria was employed, involving 47 pregnant women as subjects. Nutritional intake was measured with the semi-quantitative food frequency questionnaire (SQ-FFQ). The nutritional status of pregnant women is measured by BMI. HbA1c was measured by the turbidimetric inhibition immunoassay (TINIA) method. Analysis of research data using the Pearson product-moment correlation test and rank Spearman. The results of this study stated that there was a relationship between nutritional intake and BMI with HbA1c levels. Diagnosis of GDM and appropriate intervention can reduce the risk of complications of diabetes mellitus (DM).